PENGARUH VIDEO ANIMASI TERHADAP PENGETAHUAN IBU HAMIL TRIMESTER III TENTANG ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS DENDANG - Netty Friska Siagian; Lia Artika Sari; Herinawati Herinawati (NHM PRESS, 2022)
The coverage of exclusive breastfeeding nationally in Indonesia is 61.33%. One of the efforts to increase the percentage of exclusive breastfeeding is by conducting health education that can be done since pregnancy in order to prepare for early breastfeeding. Quasy experimental research design which is one group pretest-posttest to determine the effect of animated video media on the knowledge of third trimester pregnant women about exclusive breastfeeding. This research was conducted in the Dendang Health Center Work Area in February-June 2022. The sample of this study was 67 pregnant women using total sampling technique. The instrument used in this research is filling out a questionnaire. The statistical test used to analyze the data for the two variables was using T-Test with a significance level of 5%. The results showed that before being given an animated video about exclusive breastfeeding, most of the respondents had poor knowledge and after being given an animated video about exclusive breastfeeding, most of the respondents had good knowledge. The statistical test results obtained a p-value of 0.000 which means that there is a significant influence between animated videos on the knowledge of third trimester pregnant women about exclusive breastfeeding. The conclusion of the study is that there is a significant effect between animated videos on the knowledge of third trimester pregnant women about exclusive breastfeeding